2003
DOI: 10.1007/s11892-003-0027-8
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet xenotransplantation: Barriers and prospects

Abstract: Dramatic clinical advances indicate that pancreatic islet transplants can reliably restore euglycemia in insulin-dependent patients. However, clinical success actually highlights the pronounced deficiency of allogeneic pancreata available for islet isolation. This pressing issue has revitalized ongoing efforts to develop surrogate donor sources. Xenogeneic donors form a potential alternative tissue source because they can be generated in large numbers and are amenable to genetic engineering. However, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Importantly, therapies that are effective in promoting islet allograft survival and tolerance can show similar efficacy in promoting xenograft survival. It is unclear whether similar results can be achieved in large animal models in which vigorous innate immune responses and/or preexisting xenoreactive natural antibodies are likely to comprise a more stringent barrier to xenograft survival (45). However, our results indicate that strategic simultaneous targeting of differing immune pathways can be highly efficacious in preventing the rejection of NPI xenografts and that such approaches may form an important future component of therapeutic regimens applied in clinical islet xenotransplantation.…”
Section: Anti-lfa-1 and Islet Xenograft Prolongationmentioning
confidence: 68%
See 1 more Smart Citation
“…Importantly, therapies that are effective in promoting islet allograft survival and tolerance can show similar efficacy in promoting xenograft survival. It is unclear whether similar results can be achieved in large animal models in which vigorous innate immune responses and/or preexisting xenoreactive natural antibodies are likely to comprise a more stringent barrier to xenograft survival (45). However, our results indicate that strategic simultaneous targeting of differing immune pathways can be highly efficacious in preventing the rejection of NPI xenografts and that such approaches may form an important future component of therapeutic regimens applied in clinical islet xenotransplantation.…”
Section: Anti-lfa-1 and Islet Xenograft Prolongationmentioning
confidence: 68%
“…Unlike allograft rejection that is independent of host MHC class II expression, porcine xenograft rejection was found to be entirely dependent on this indirect pathway (2). Importantly, T-cell-dependent antibody responses to allografts or xenografts are presumptive evidence of this "indirect" antigen recognition since T-B-cell collaboration requires interaction of helper T-cells, with antigens acquired and presented by the specific B-cell (45). We have frequently found that islet xenografts demonstrate an exaggerated antibody response relative to allografted animals, suggestive of strong indirect T-cell reactivity in vivo (R.G.G.…”
Section: Anti-lfa-1 and Islet Xenograft Prolongationmentioning
confidence: 99%
“…While fully immune competent transplant recipients possess a broad repertoire of pathways available to mount a response to non-self tissue, it is becoming increasingly apparent that the characteristics of xenograft immunity depend both on the tissue/organ grafted and the specific type of phylogeneic difference between donor and recipient [6, 14]. Therefore, one must examine the requirements for T-cell-dependent xenograft rejection using defined tissues/organs of interest and particular inter-species transplant combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on the removal or reduction of antibodies or antibody responses show promise [2–5]. However, even if hyperacute rejection can be prevented, adaptive T-cell dependent humoral and cellular mechanisms are capable of aggressive xenograft rejection [6, 7]. The role of CD4 + T-cells in the rejection of cardiac allografts and xenografts is well established.…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes play an important role not only in chronic rejection but also in acute rejection of heart transplants . Adaptive T cells relying on humoral and cellular mechanisms can actively induce xenograft rejection . The role of CD4 + T cells in the rejection of heart transplants has been well established.…”
Section: Discussionmentioning
confidence: 99%